2013
DOI: 10.1210/jc.2013-1113
|View full text |Cite
|
Sign up to set email alerts
|

Prepubertal Girls With Turner Syndrome and Children With Isolated SHOX Deficiency Have Similar Bone Geometry at the Radius

Abstract: Context:The low bone mineral density (BMD) and alterations in bone geometry observed in patients with Turner syndrome (TS) are likely caused by hypergonadotropic hypogonadism and/or by haploinsufficiency of the SHOX gene. Objective:Our objective was to compare BMD, bone geometry, and strength at the radius between prepubertal girls with TS and children with isolated SHOX deficiency (SHOX-D) to test the hypothesis that the TS radial bone phenotype may be caused by SHOX-D. Design and Setting:This comparative cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…SHOX-D has been demonstrated in a number of conditions including Léri-Weill syndrome, Langer mesomelic dysplasia, TS, and in children with ISS3,43,44). Interestingly, prepubertal girls with TS and children with isolated SHOX-D show similar bone geometry at the radius4). In a two-year randomized trial, GH treatment (0.05 mg/kg daily) improved growth in patients with SHOX-D45).…”
Section: Shox Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…SHOX-D has been demonstrated in a number of conditions including Léri-Weill syndrome, Langer mesomelic dysplasia, TS, and in children with ISS3,43,44). Interestingly, prepubertal girls with TS and children with isolated SHOX-D show similar bone geometry at the radius4). In a two-year randomized trial, GH treatment (0.05 mg/kg daily) improved growth in patients with SHOX-D45).…”
Section: Shox Deficiencymentioning
confidence: 99%
“…Recent findings indicate that haploinsufficiency of the SHOX gene located in the pseudoautosomal region of the sex chromosomes as one of the leading causes3). In this regard it has been shown that bone alteration of the hand and wrist are similar between girls with TS and patients with SHOX haploinsufficiency4). The final height in untreated girls with TS is approximately 20 cm below that of normal female subjects2).…”
Section: Turner Syndromementioning
confidence: 99%
“…A relatively low frequency of LWD in Turner patients despite SHOX deficiency is consistent with attenuated estrogen production in these individuals. Soucek et al [2013] investigated bone mineral density and bone geometry in prepubertal patients with SHOX haploinsufficiency. They found a significantly increased total bone area, decreased relative cortical bone area, and a thin cortex.…”
Section: Clinical Manifestations Of Patients With Shox Haploinsufficimentioning
confidence: 99%
“…investigated bone mineral density and bone geometry in 10 prepubertal patients with SHOX deficiency and 22 patients with Turner syndrome (26). They found that patients of both groups had a thin bone cortex and an enlarged total bone area at the diaphysis of the radius compared with control individuals.…”
Section: Changes In Bone Geometry Andbone Mineral Densitymentioning
confidence: 99%
“…Furthermore, a longitudinal study of a female patient with SHOX deficiency and normal ovarian function showed age-appropriate skeletal maturation before puberty and rapidly advanced bone age during puberty (36). On the other hand, since Soucek et al revealed a significant difference in bone geometry between prepubertal patients with the 46,XX karyotype and prepubertal Turner females, it is likely that some factors other than estrogens may also underlie relatively mild skeletal features in Turner females (26). Soucek et al suggested karyotype mosaicism as one of the possible candidates for such factors (26).…”
Section: Phenotypic Determinantsmentioning
confidence: 99%